2010
DOI: 10.1158/0008-5472.can-09-4596
|View full text |Cite
|
Sign up to set email alerts
|

Melanocyte-Stimulating Hormone Directly Enhances UV-Induced DNA Repair in Keratinocytes by a Xeroderma Pigmentosum Group A–Dependent Mechanism

Abstract: Melanocyte-stimulating hormone (MSH) reduces UV-induced DNA damage through the induction of pigmentation. In this study, we provide evidence that MSH also enhances DNA repair in skin keratinocytes by modulating the function of DNA repair molecules. Intracutaneous injection of MSH prevented UV-induced DNA damage in human and mouse skin independent of its effects on melanogenesis. In keratinocytes, MSH bound to the melanocyte melanocortin receptor type 1 and activated adenylate cyclase activity, which in turn ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
5
32
1
1
Order By: Relevance
“…Here we also demonstrated that dietary GSPs induces or augments XPA nuclear translocation and then activates the core incision complex in the NER system. Similar observations related with the role of XPA in DNA repair in UVB-exposed skin cells were also found by the treatment of a-melanocytestimulating hormone (35). Stoner et al have studied the effect of diet containing freeze-dried black raspberries on chemical carcinogen N-nitrosomethylbenzylamineinduced dysregulated genes in rat esophagus (36).…”
Section: Nonsupporting
confidence: 55%
“…Here we also demonstrated that dietary GSPs induces or augments XPA nuclear translocation and then activates the core incision complex in the NER system. Similar observations related with the role of XPA in DNA repair in UVB-exposed skin cells were also found by the treatment of a-melanocytestimulating hormone (35). Stoner et al have studied the effect of diet containing freeze-dried black raspberries on chemical carcinogen N-nitrosomethylbenzylamineinduced dysregulated genes in rat esophagus (36).…”
Section: Nonsupporting
confidence: 55%
“…These diseases are characterized at the level of the skin by extreme sensitivity to sunlight, resulting in sunburn, pigmentation changes, an early onset of the appearance of skin aging signs and a greatly elevated incidence of skin cancers in particular for XP disorder [12]. These changes can be explained by long lasting DNA damages that induces prolonged cellular inflammation through the activation of the NF-κB pathway [2,13,14,15,16] and an acquired immune deficiency [17] as well as rapid accumulation of mutation leading to cell apoptosis, senescence and cell tumorigenesis [18,19,20,21].…”
Section: Skin Dna Damage and Repairmentioning
confidence: 99%
“…The activation of the Melanocortin Receptor 1 (MCR1) by either its natural ligand, the α-Melanocyte stimulating Hormone αMSH or synthetic analogs [20,21] can enhance the DNA repair activity in cells. Also two interleukins (IL), IL12 and IL23 known to display anti-tumor activity [45,46,47,48] have been shown to accelerate the repair of UVB induced CPDs [2].…”
Section: Antioxidants Combat Oxidative Stressmentioning
confidence: 99%
“…The activation of the Melanocortin Receptor 1 (MCR1) by either its natural ligand, the α-Melanocyte stimulating Hormone αMSH or synthetic analogs [17,18] can enhance the DNA repair activity in cells. Also two interleukins (IL), IL12 and IL23, known to display anti-tumor activity [19][20][21][22], have been shown to accelerate the repair of UVB induced CPDs. Activation of detoxifying mechanisms such as the NRf2 pathway may enhance also DNA repair [23].…”
Section: Inflammation and Dna Repairmentioning
confidence: 99%